An Analysis of Hànzì Stroke Errors in 11th Grade Hospitality Students at State Vocational High School 5 Barru - Muh. Khaerul Adha Syam; Abdul Kasim Achmad; Arini Junaeny; Lin Xinyue (International Journal of Chinese Interdisciplinary Studies, 2024)
This study aims to determine the types of stroke errors in the Chinese character笔画 (bǐ huà) and factors that influence stroke errors in Chinese characters笔画 (bǐ huà). The subjects of this study were 8 students of class XI Hospitality at SMK Negeri 5 Barru. This type of research is descriptive by utilizing qualitative data consisting of a writing test汉字( hànzì), and interviews (in depth interview). The data were then analyzed using the Miles and Huberman model data analysis technique combined with the Error and Mistake theory. Where the data was collected later, the data was identified, explaining the error, clarifying the error, and finally evaluating the error. The results of this study showed that all students made errors in the strokes of the hànzì笔画 (bǐ huà), the most frequently incorrect stroke is the 撇stroke. ( piě) 63 times and the stroke 横( héng) 40 times, 2 out of 8 students drew han zi instead of writing it, and 2 out of 8 students made mistakes in writing the Mandarin character汉字 (hànzì) with the respective characters家,想,鱼, and他so that the characters are incomplete or unrecognizable.